Virtual Drama in Literature Education: Enhancing Language Learning Amid Challenges - Thayyib , Magfirah; Wahibah, Wahibah; Ismayanti, Devi; Zainuddin, Andi Husni A. (International Journal of Asian Education, 2025)
Literature education is essential for enhancing students’ language competence, critical thinking, and engagement with literary texts. This study explores the implementation of a virtual drama project in literature classes for English Education students at IAIN Palopo, examining their responses, benefits, and challenges. Employing a descriptive-quantitative approach with qualitative elements, data were collected from 100 students across six classes through a structured questionnaire. Descriptive statistics and thematic analysis were used to analyze the findings. Results indicate that 72% of students viewed the virtual drama project as an engaging and effective learning tool, reporting improved language competence, pronunciation, confidence, and higher-order thinking skills. Additionally, 15% highlighted personal growth, citing increased self-confidence and creativity. However, 29% faced acting difficulties, struggling with emotional expression and performance adaptation in a virtual format. Technical barriers, such as poor internet connectivity (5%) and device limitations (2%), also hindered some students’ experiences. Despite these challenges, the study underscores virtual drama’s potential as an innovative pedagogical approach in literature education. Educators can enhance the effectiveness of virtual drama projects by integrating acting workshops, technological support, and stronger links to literary analysis. These findings contribute to the evolving landscape of digital literature education, offering insights for future curriculum design and pedagogical innovation in language learning.